Development and Standardisation of Adolescent at Risk Screening Scale (ARSS) - Biswas, Sukanya; Sharma, Poonam (JOURNAL OF INDIAN EDUCATION, 2023)
With the dearth of adolescent at risk measurement scales in India and the need for the same in the context of the rising popularity of at risk adolescent programmes, a culture-specific scale to screen at risk adolescents is imperative. With this background, the current study aimed to develop and standardise a scale to screen at risk adolescents in India. The objectives were to— (i) construct a comprehensive scale for screening at risk adolescents; (ii) select and test the measurability of items in the at risk adolescent’s scale and; (iii) test the reliability and validity of the scale. The study was predominantly following the scale design. It was conducted in three main stages—scale development, field testing of the scale and standardisation. A total of 100 adolescents from Grades VII–X, belonging to different backgrounds, participated in the study. The age group of the adolescents ranged from 13–16 years. Convenience sampling was followed. The items were developed after an extensive literature review. Face and content validation was established. Item analysis, correlation and reliability tests were used. The reliability of the test-retest was 0.892 and the Guttman Split Half Coefficient was 0.867, all indicating high reliability.